Association of serum methylglyoxal with endothelial dysfunction in patients with type 2 diabetes - Yu, Shanshan; Jin, Xinyan; Xu, Yuanying; Liu, Zhao; Lu, Jun; Gao, Jie; Sha, Wenjun; Lei, Tao (Frontiers in Pharmacology, 2026)
AimsTo explore the correlation between serum Methylglyoxal (MGO) and endothelial dysfunction in patients with type 2 diabetes mellitus, and to evaluate the clinical value of MGO in the development of diabetes mellitus and its complications.MethodsIn this cross-sectional study, we enrolled 250 patients diagnosed with T2MD. Based on flow-mediated dilation (FMD) measurements, the patients were categorized into normal endothelial function group (FMD ≥6.4%, n = 61) and endothelial dysfunction group (FMD <6.4%, n = 189). Analysis of the relationship between MGO and FMD was conducted via Spearman’s correlation, partial correlation, and multiple logistic regression. An ROC curve analysis was utilized to quantify the predictive performance of MGO for endothelial function.ResultsEndothelial dysfunction was observed in 189 (76%) patients with type 2 diabetes. Patients with endothelial dysfunction had higher concentration of MGO in the serum (P < 0.001) than those without endothelial dysfunction. Spearman correlation analysis showed that there was a significantly negative correlation between FMD and MGO (R = −0.611, p < 0.001), and this negative correlation remained significant upon adjustment for age and sex. (R = −0.36, p < 0.001). Logistic regression analysis identified MGO as an independent risk factor for endothelial dysfunction (OR 1.099, (1.06–1.14), p < 0.001), and the odds of endothelial dysfunction increased 2.67-fold per standard deviation (SD) increment in MGO levels (OR: 2.67 (1.78–4.01), p < 0.001) (Model 1). After adjusting for gender, age, BMI, course of disease, hypertension, smoking and alcohol consumption (model 2) as well as HbA1c, HOMA-IR, C-reactive protein and TG (model 3), similar results were obtained. Restricted cubic spline (RCS) analysis revealed a significant non-linear does-response relationship between MGO levels and endothelial function (Poverall<0.001, Pnon-linearing<0.001). Subgroup analyses demonstrated that the association between MGO levels and endothelial function remained consistent across various strata, including age, sex, and comoribidities (all Pinteraction>0.05). Receiver operating characteristic (ROC) curve: the area of under the ROC curve (AUC) for MGO was 0.785 (OR: 0.73-0.84, p < 0.001).ConclusionMGO was significantly inversely associated with FMD and endothelial function in T2DM patients, and can be used as a biomarker to assess vascular endothelial health. Detection of serum MGO levels has clinical significance in the prevention of early diabetic vascular disease.